Virtual Reality and Augmented Reality in Human Resources: The Manufacturing Sector Perspective - Constanca FERNANDES; Viviana MEIRINHOS; Ana C. RODRIGUES (Communications of International Proceedings, 2021)
Human Resources Management and Development (HRMD) has been evolving simultaneously with the technological advances and supporting organisations in the industry in the contemporary competitive environment. Virtual Reality (VR) and Augmented Reality (AR) are innovative technologies with a recognised potential in several fields and in industry and promising tools to support the HRMD processes in the manufacturing sector. This study analyses the perceptions of the potential of VR and AR in managing people by HRMD professionals operating in the manufacturing sector. Two online Focus Group were conducted with Portuguese HRMD professionals (n=14), to gather data on their conceptualisation, experience and perspective about VR and AR. The results suggest that knowledge on these technologies and associated concepts are not very clear and the experiences with these tools are not frequent. Gaming was the context identified as the most commonly associated to VR and AR knowledge and experience. VR and AR were assumed to be strong allied tools to HRMD professionals, for Human Resources (HR) area and for a set of processes: training, onboarding, recruitment and selection, organisational culture, attraction, and retention. Within these, training was the HR practice more indicated as with the most potential for it. These results will contribute to HR professional’s awareness on the potential of VR and AR in HR and supported them to identify specific potentialities in HR processes. We suggest that future studies explore other activity sectors of economy activity and more deeply the potentialities of VR and AR in each of the HR processes.
Keywords: Augmented Reality; Human Resources; Manufacturing Sector; Virtual Reality